Preradicals, closure operators in R-Mod and connection between them - Kashu, A.I. (Algebra and Discrete Mathematics, 2014)
For a module category R-Mod the class PR of preradicals and the class CO of closure operators are studied. The relations between these classes are realized by three mappings: Φ : CO → PR and Ψ₁, Ψ₂ : PR → CO. The impact of these mappings on the operations in PR and CO (meet, join, product, coproduct) is investigated. It is established that in most cases the considered mappings preserve the lattice operations (meet and join), while the other two operations are converted one into another (i.e. the product into the coproduct and vice versa).